Effect of large-span three-sided culvert configuration on its performance at service and ultimate loading conditions - Ramadan, Safwat H.; Hesham El Naggar, M. (Tunnelling and underground space technology, 2022)
•Assuming uniform contact pressure underneath strip footings of TSCs is realistic.•The maximum backfill height at failure decreases as the sidewall height increases.•The sidewall height governs the locations of failure and plastic hinges formation.•Short sidewalls rotated as a rigid body as the backfill height increased.•Short TSC sidewall height and footing with pedestal offer favorable performance. The configuration of large-span reinforced concrete (RC) three-sided culverts (TSCs) with flat top slab can affect their geo-structural performance. Therefore, the measured responses of an instrumented 13.5-m-span TSC under 3.0 m of backfill were analyzed to elucidate the effect of its configuration on the pressure distribution along the top slab and sidewalls as well as underneath the footing. The field monitoring data were utilized to validate two-dimensional (2D) nonlinear finite element models (FEMs) that were then employed to analyze the culvert response at service loading conditions. The validated nonlinear 2D FEM was then extended to analyze the ultimate limit state (ULS) response at deeper backfill heights. In addition, the influence of the culvert sidewall and footing pedestal heights on the footing-culvert system performance was investigated. To further examine the effect of sidewall height on the structural capacity of the precast culvert unit, 3D nonlinear FEMs were developed to simulate a laboratory load testing for the precast unit of the subject TSC with different sidewall heights. The results from the 2D FEMs demonstrated non-uniform vertical earth pressure distribution on the top slab at all backfill heights. The height of the culvert sidewall was found to influence the location of failure surface and the maximum backfill height at failure. Moreover, the results clearly demonstrated significant influence of sidewall configuration on the performance of the footing-culvert system. Relatively short sidewall with long footing pedestal performs better than long sidewalls with short pedestals. The 3D FEMs showed that the precast unit structural capacity could decrease by up to 18% due to increased sidewall height.